Effectiveness of Childbirth Services among Health Centers of Cagayan de Oro City - Dalman, Judith T. (JPAIR Multidisciplinary Research, 2008)
This study aimed to evaluate the effectiveness of childbirth services at the health centers of Cagayan de Oro City. The respondents were mothers who had given birth at these centers, selected purposively based on their use of the services. The study assessed the mothers’ profiles, including maternal history (number of deliveries and illnesses), and the effectiveness of childbirth services, focusing on care during labor, delivery, and postpartum. Using a descriptive and evaluative survey method, data were analyzed through descriptive statistics such as frequency, percentage, and weighted mean, with an F-test applied to test differences in effectiveness levels. Conducted in February 2008, the findings revealed that most respondents agreed on the effectiveness of care provided but noted no significant differences across factors. Among the three categories of health care services, health workers demonstrated positive caring behavior toward mothers. Most respondents availing of these services were from low-income households or below the poverty line. However, mothers with prior illnesses were less trusting of health center services due to perceived risks. While many factors did not significantly impact the effectiveness of childbirth services, the study highlighted areas for improvement in service delivery. The findings serve as a basis for decision-making and policy formulation to enhance maternal care at health centers in Cagayan de Oro City.